Educational expansion and income distribution. A Micro-Simulation for Ceará - Francisco H. G. Ferreira; Phillippe George Leite (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2002)
Does more education really mean less poverty and less inequality? How much less? What are the transmission mechanisms? This paper presents the results of a micro-simulation exercise for the Brazilian State of Ceará, which suggests that broad-based policies aimed at increasing educational attainment would have substantial impacts on poverty reduction, but muted effects on inequality. These results are highly dependent on assumptions about the behaviour of returns to education, both for the distribution of earnings and for the distribution of household income per capita. A large share of the poverty reducing effect of more education operates through greater incentives for labour force participation among the poor, and through reductions in fertility. Both of these effects function largely through decisions made by poor women.
Keywords: C15; D31; I31; J13; J22; 330; education; poverty; inequality; Bildungsniveau; Bildungsertrag; Armut; Einkommensverteilung; Ceara